2018
DOI: 10.1530/erc-18-0106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prognostic value of PAX2 and PTEN in endometrial carcinogenesis

Abstract: E Rewcastle et al.PAX2 in endometrial neoplasia 981-991 AbstractIn order to avoid the consequences of over-and under-treatment of endometrial hyperplasia, diagnostic accuracy and progression risk assessment must be improved. The aim of this study was to assess whether PAX2 or PTEN expression could predict progression-free survival in endometrial intraepithelial neoplasia (EIN) and endometrial endometrioid carcinoma (EEC). Immunohistochemistry for detection of PAX2 and PTEN was performed on 348 endometrial samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In addition, the intercellular transfer of hsa-miR-4306 by platelet microparticles inhibits the migration of human monocyte-derived macrophages through the VEGFA/ERK1/2/NF-κB signaling pathway, which may influence the immunological environment at the maternal–fetal interface ( Yang et al, 2019 ). In addition, its target gene PAX2 acts as a tumor suppressor in endometrial carcinogenesis ( Raffone et al, 2019 ), which is an accurate marker of precancerous endometrial hyperplasia ( Rewcastle et al, 2018 ). The reduction of PAX2 expression in murine oviductal cells enhances estrogen receptor signaling ( Colina et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intercellular transfer of hsa-miR-4306 by platelet microparticles inhibits the migration of human monocyte-derived macrophages through the VEGFA/ERK1/2/NF-κB signaling pathway, which may influence the immunological environment at the maternal–fetal interface ( Yang et al, 2019 ). In addition, its target gene PAX2 acts as a tumor suppressor in endometrial carcinogenesis ( Raffone et al, 2019 ), which is an accurate marker of precancerous endometrial hyperplasia ( Rewcastle et al, 2018 ). The reduction of PAX2 expression in murine oviductal cells enhances estrogen receptor signaling ( Colina et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining of our clinical samples showed that PAX2 protein was absent in 90.91% of EEC and 75.68% of EIN cases, indicating that progression from EIN to ECC induces gradual loss of PAX2 protein expression. Rewcastle et al also found decreasing PAX2 expression from normal endometrium to EIN and EEC tissues during IHC analysis [23]. These findings suggest that PAX2 inactivity is involved in the early carcinogenesis of EEC.…”
Section: Discussionmentioning
confidence: 88%
“…(8) Other study done byRewcastle et al (2018)showed thata progressive decrease in PAX2 expression from proliferative endometrium to EIN to EEC were observed. (17) A study done by Trabzonlu et al (2019)showed that 73.3%of EIN cases had decreased PAX2 stainingas compare tonormalendometrial glands. (18) Only one study found todisagreed with this study done by Kahraman et al (2012) showed that PAX2 expression was detected in all of the endometrial samples: -80.8% in proliferative endometrium, 92.7% and 99.2% in atypical hyperplasia and endometrial adenocarcinoma respectively).…”
Section: Discussionmentioning
confidence: 97%